2008
DOI: 10.1016/j.matbio.2007.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptide sequence in perlecan domain IV supports cell adhesion, spreading and FAK activation

Abstract: Perlecan/HSPG2 is a large, multi-domain, multifunctional heparan sulfate proteoglycan with a wide tissue distribution. With the exception of its unique domain I, each of perlecan's other four domains shares sequence similarity to other protein families including low density lipoprotein (LDL) receptor, laminin alpha chain, neural cell adhesion molecule (NCAM), immunoglobulin (Ig) superfamily members, and epidermal growth factor (EGF). Previous studies demonstrated that glycosaminoglycan-bearing perlecan domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…The intact perlecan molecule that is produced by cultured acinar cells is expected to be modified by heparan sulfate chains that in previous studies were found to conceal the adhesive domain IV motifs. 11 Fibroblasts cultured on intact perlecan failed to make stable focal adhesion contacts because of the antiadhesive activity of gagosylated perlecan domain I. 23 Consistent with this, our studies showed less FAK activation and, more strikingly, a failure to cluster phosphorylated FAK to sites of focal adhesions when cells were cultured on plastic.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The intact perlecan molecule that is produced by cultured acinar cells is expected to be modified by heparan sulfate chains that in previous studies were found to conceal the adhesive domain IV motifs. 11 Fibroblasts cultured on intact perlecan failed to make stable focal adhesion contacts because of the antiadhesive activity of gagosylated perlecan domain I. 23 Consistent with this, our studies showed less FAK activation and, more strikingly, a failure to cluster phosphorylated FAK to sites of focal adhesions when cells were cultured on plastic.…”
Section: Discussionsupporting
confidence: 80%
“…The functionality of the cultured salivary acinar cells in vitro is confirmed by their secretion and organization of their own basement membrane including the critical component perlecan that can support further growth and differentiation by virtue of its ability to interact with cell adhesion molecules that can influence integrin-mediated events. 11,15 Uniquely, no non-human-derived material was needed for isolation or culture of the acinar cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations